Developing teaching material based on realistic mathematics andoriented to the mathematical reasoning and mathematical communication - Habsah, Fitria (Jurnal Riset Pendidikan Matematika, 2017)
This research aims to produce mathematics textbook for grade VII junior high school students based on realistic mathematics and oriented to the mathematical reasoning and mathematical communication. The quality is determined based on Nieveen criteria, including validity, practicality, and effectiveness.This study was a research and development and used Borg & Gall model. The subject of this research were the students of SMPN 2 Pujon-Kabupaten Malang, that is 30 students in an experimental class (using the developed textbook) and 29 students in a control class (using BSE book from the government). The teaching material was categorized valid if the expert’s judgment at least is categorized as "good". The teaching material was categorized practical if both of teachers and students assessment at least categorized as "good". The teaching material was categorized effectively if minimum 75% of student scores at least is categorized as "good" for the mathematical reasoning test and mathematical communication test. This research resulted in a valid, practical, and effective teaching material. The resulted of the validation show that material teaching is valid. The resulted of teachers and students assessment show that the product is practical. The tests scores show that the product is effective. Percentage of students who categorized at least as "good" is 83,33% for the mathematical reasoning and 86,67% for the mathematical communication. The resulted of statistic test shows that the product more effective than the BSE book from the government in terms of mathematical reasoning and mathematical communication.